DEVELOPING A PROBLEM-BASED LEARNING BASED LKPD TO IMPROVE THE READING COMPREHENSION SKILLS - Apriani, Nur Pika Indah; Maufur, Syibli; Ummah, Inayatul (Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study was motivated by the low reading comprehension skills of elementary school students, which require innovative learning strategies to improve student engagement and understanding. The objective of this study was to develop a Problem-Based Learning (PBL)-based Student Worksheet (LKPD) and examine its feasibility and its potential to improve the reading comprehension skills of fourth-grade students. This study employed a Research and Development (R&D) method using a simplified Borg and Gall model. The participants were fourth-grade students of SDN Sukapura 3. Data were collected through observation, interviews, questionnaires, and reading comprehension tests, while data analysis was conducted using validation percentage analysis and N-Gain analysis. The results indicated that the developed PBL-based LKPD was categorized as highly feasible, with validation scores of 94.4% from media experts, 91.6% from language experts, and 100% from material experts. The implementation of the LKPD was also associated with an increase in students’ average reading comprehension scores from 63.6 in the pre-test to 86.8 in the post-test, with an N-Gain score of 0.632, which falls into the moderate category. These findings suggest that the PBL-based LKPD has the potential to improve students’ reading comprehension skills and can serve as an innovative teaching material in elementary schools. However, since this study used a one-group pretest-posttest design without a control group, the findings should be interpreted cautiously.